Influence of Poly-L-Lactic Acid Scaffold's Pore Size on the Proliferation and Differentiation of Dental Pulp Stem Cells - Conde,Cristian Muniz (2015)
The aim of this study was to evaluate the influence of the poly-L-lactic acid (PLLA)-based scaffold's pore size on the proliferation and differentiation of dental pulp stem cells (DPSCs). The scaffolds were prepared in pulp chambers of 1-mm-thick tooth slices from third molars using salt crystals (150-250 µm or 251-450 µm) as porogen. DPSC (1x105 cells) were seeded in the scaffolds with different pore sizes, and cultured in 24-well plates. The cell proliferation was evaluated using the WST-1 assay after 3-21 days. Furthermore, RT-PCR was used to assess the differentiation of the DPSCs into odontoblasts, using markers of odontoblastic differentiation (DSPP, DSP-1 and MEPE). RNA from human odontoblasts was used as control. Cell proliferation rate was similar in both scaffolds except at the 14th day period, in which the cells seeded in the scaffolds with larger pores showed higher proliferation (p<0.05). After 21 days DPSCs seeded in both evaluated scaffolds were able of expressing odontoblastic markers DMP-1, DSPP and MEPE. In summary, both scaffolds tested in this study allowed the proliferation and differentiation of DPSCs into odontoblast-like cells.